Faba Bean Flour and Protein Isolate as Partial Substitutes in Wheat-Triticale Bread: A Technological and Sensory Properties - Maravić, Nikola; Hadnađev, Miroslav; Dapčević-Hadnađev, Tamara; Pestorić, Mladenka; Tomić, Jelena (Food and Feed Research, 2024)
The incorporation of faba bean flour (FBF) and protein isolate (FBI) into wheat-triticale flour blends is a potential promising strategy to enhance the nutritional and functional properties of bread. This study aimed to investigate the potential of these ingredients from both technological and sensory perspectives. Multiple analyses were conducted, including chemical composition, texture profile analysis, color, specific volume and sensory properties of breads made with a blend of wheat and triticale flours (70:30). Part of the blend was substituted with either 20% faba bean flour or 7.2% faba bean protein isolate to ensure an equal proportion of faba bean protein in the final formulations. The results showed a significant increase in protein content for both FBF and FBPI breads, with the faba bean protein isolate also increasing the ash content. Texture profile analysis (TPA) indicated that the substitutions affected bread properties by increasing hardness, gumminess, and chewiness, particularly in bread with FBI. However, cohesiveness, springiness, and resilience decreased similarly in both cases. Additionally, the specific volume decreased with the addition of faba bean flour and protein, especially in FBI bread. From the colour aspect, analysis revealed a darker hue and a more pronounced reddish nuance in the bread crust in FBF and FBI breads. Sensory evaluation indicated a slightly lower overall likeability with faba bean addition, yet the breads remained acceptable to the panellists. Detailed sensory analysis supported the TPA findings and colour differentiation, showing higher values for hardness, crust compactness, and crumbliness. Texture and color were rated lower compared to the control sample. Moreover, both FBF and FBI breads exhibited higher overall odour intensity. Specifically, bread with the protein isolate had less uniform pores and a more pronounced flour/cereal/bran odour. In contrast, bread with faba bean flour had more uniform pores but a noticeable bitterness. In conclusion, this study demonstrates that faba bean flour and protein isolate can be used as partial substitutes in wheat-triticale flour blends to produce bread with acceptable properties. This leaves room for future in-depth analysis and modifications to address the identified challenges.
Keywords: faba bean; protein isolate; triticale; bread